Experimental research on optimization of compression molding process parameters of pineapple rind residue - Tian, Kunpeng; Zhang, Bin; Huang, Jicheng; Liu, Haolu; Shen, Cheng; Li, Xianwang; Chen, Qiaomin (International Journal of Agricultural and Biological Engineering, 2021)
Currently, the process parameters for compression molding of pineapple rind residue are not clear. In view of this problem, a single die hole compression molding test device was designed in this study, and the force of material in a mold hole was analyzed. Using the test device, a three-factor three-level orthogonal test was carried out by using the particle size, moisture content, and die hole length-to-diameter ratio of pineapple rind residue as the factors and the particle molding rate, relax density, and specific energy consumption as the indicators. The test results were analyzed by range analysis, variance analysis, and fuzzy comprehensive evaluation. The test results show that the main and secondary factors affecting the comprehensive performance of pineapple rind residue compression molding are length-to-diameter ratio, particle size, and moisture content. The optimal parameter combination is the material particle size of 6-9 mm, moisture content of 16%, and length-to-diameter ratio of 4:1. The best indicators under these conditions are particle molding rate of 97.80%, relax density of 1.32 g/cm, and specific energy consumption of 44.17 J/g. These research results can provide a reference for the selection of processing parameters and the design of molding equipment. Keywords: pineapple rind residue, compression molding, waste utilization, pellet forming, orthogonal test, process parameter optimization DOI: 10.25165/j.ijabe.20211403.6041 Citation: Tian K P, Zhang B, Huang J C, Liu H L, Shen C, Li X W, Chen Q M. Experimental research on optimization of compression molding process parameters of pineapple rind residue. Int J Agric & Biol Eng, 2021; 14(3): 221–227.